Role of Nutrients and Phyto-compounds in the Modulation of Antimicrobial Resistance - Harakeh, Steve; Khan, Imran; B. Almasaudi, Saad; I. Azhar, Esam; Al- Jaouni, Soad; Niedzweicki, Aleksandra (Current Pharmaceutical Design, 2012)
Background: Antimicrobial resistance is quickly spreading and has become a major public health problem worldwide. If this issue is not resolved, it may cause a shift back to the pre-antibiotics era and infectious disease will again be a serious problem, especially in developing countries. Since the discovery of antibiotics, bacterial resistance has emerged, enabling certain bacteria to withstand antibiotic action. The emergence of antibiotic resistance is fueled by excessive and improper use of antimicrobial agents, especially in developing countries. For this reason, alternatives to or modifications of current treatment methods have been sought. The aim of this review is to highlight the possible synergies of various agents that can augment antibiotic activities. Methods: A structured literature search was conducted using only papers that have been published in PubMed with the focus on the agents that are likely to modulate antimicrobial resistance. In this review, data was retrieved from the literature regarding the possible synergies that exist between commercially available antimicrobial drugs with agents of interest. The papers included were summarized and analyzed, critiqued and compared for their contents using a conceptual frame-work. Results: In total, one hundred and twenty six papers were reviewed. The number of papers that dealt with the different topics included are as follows (): emergence of antimicrobial resistance (22), bioactive phyto-compounds (36) (phytobiologics, and phytochemicals), Antioxidants (40) (N-acetylcysteine, Ambroxol, Ascorbic acid, Glutathione and vitamin E), Peptide synergies (14) (Synthetic cationic α-helical AMPs, CopA3, Alafosfalin, PMAP-36, Phosphonopeptide L-norvalyl-L-1-aminoethylphosphonic acid and norcardicin-A), nano-antibiotics (10), drug-compound interactions (4).This review addressed the new strategies using the above compounds in the modulation of antimicrobial resistance to avoid issues related to resistance of bacteria to antibiotics. Conclusions: The findings of this review confirm that certain compounds can act in synergy with currently used antimicrobials to enhance the potential of antimicrobial agents and thus to reduce the emergence of antimicrobial resistance. Some of these synergies are already being used to enhance the potential of currently used antimicrobial agents. More studies need to be conducted to better understand the mechanism of action of such compounds, and based on the results, new compounds may be sought.
Keywords: bacteria